Multiple hamartoma syndrome: Clinicoradiological evaluation and histopathological correlation with brief review of literature - Emma Monga; Prashant K Gupta; Avinash Munshi; Sudhi Agarwal (Wolters Kluwer Medknow Publications, 2014)
Cowden syndrome (CS) or multiple hamartoma syndromes (MHSs) is an uncommon condition and characterized by mucocutaneous lesions which may be associated with the lesions of breast, thyroid, gastrointestinal tract, skin, and often of central nervous system. A thorough evaluation of Cowden's disease is essential due to increased risk of malignancy in an organ or system of the affected patients. We are reporting a case of female patient who presented with multiple mucocutaneous papilloma associated with involvement of multiple organs and systems. The diagnosis was confirmed by multimodality diagnostic approach. This rare entity has not being reviewed in Indian literature till date. Being a rare case, we are discussing MHS with its clinicoradiological and histopathological correlation along with brief review of literature.